Economies of writing : revaluations in rhetoric and composition - Horner, Bruce, 1957-; Nordquist, Brice; Ryan, Susan M., Ph. D. (Utah State University Press, 2017)
"Advances scholarship on political economies of writing and writing instruction, considering those economies in terms of course subject, pedagogy, technology, and social practice. Challenges dominant ideologies of writing, writing skills, writing assessment, language, technology, and public rhetoric by revealing the complex and shifting valuations of writing practices"--Provided by publisher